Will consumers substitute meat with legumes? A clustered binational perspective - Dominic Lemken; Achim Spiller; Birgit Schulze-Ehlers (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2018)
The substitution of meat with legumes is one way of making food consumption more sustainable. The substitution would ease the debate on food security and is aligned with the recommendations of climate change experts. The stagnation or decline of meat consumption in many developed countries and the emerging market for meat alternatives, point at shifting preferences from animal to plant based protein, such as legumes. While consumers' attitudes towards meat consumption are reasonably well researched, little is known about consumers' willingness to change their dietary habits from meat to plant based protein. This article explores consumers' acceptance of replacing meat with legumes, acceptance of meat alternatives made from legumes and acceptance of processed legumes in general. Consumer samples were drawn from Germany (GER: N=633) and New Zealand (NZ: N=445). The samples reflect the underlying age, gender and income distribution. Separate Latent Class Analyses revealed five consumer segments in each of the samples. In both countries, a large segment has no intention to substitute, while one segment frequently substitutes. A third segment of both countries has no intention to substitute, but considers processed legume products, if not marketed as an alternative to meat. Other segments capture country specific preferences for meat alternatives, as well as a segment that rather substitutes meat directly with certain legumes than having processed meat alternatives. Self-efficacy, i.e. the perceived ability to reduce meat, is a key barrier that hinders substitution. We discuss segment specific findings and how to develop on consumer's acceptance of substitution.
Keywords: 330